The Functional Tactile Object Recognition Test: A Unidimensional Measure With Excellent Internal Consistency for Haptic Sensing of Real Objects After Stroke - Carey, Leeanne M.; Mak-Yuen, Yvonne Y. K.; Matyas, Thomas A. (Frontiers in Neuroscience, 2020)
Introduction Our hands, with their exquisite sensors, work in concert with our sensing brain to extract sensory attributes of objects as we engage in daily activities. One in two people with stroke experience impaired body sensation, with negative impact on hand use and return to previous valued activities. Valid, quantitative tools are critical to measure somatosensory impairment after stroke. The functional Tactile Object Recognition Test (fTORT) is a quantitative measure of tactile (haptic) object recognition designed to test one’s ability to recognize everyday objects across seven sensory attributes using 14 object sets. However, to date knowledge of the nature of object recognition errors is limited, and the internal consistency of performance across item scores and dimensionality of the measure have not been established. Objectives To describe the original development and construction of the test, characterise the distribution and nature of performance errors after stroke, and to evaluate the internal consistency of item scores and dimensionality of the functional Tactile Object Recognition Test. Method Data from existing cohorts of stroke survivors (n=115) who were assessed on the fTORT quantitative measure of sensory performance was extracted and pooled. Item and scale analyses were conducted on the raw item data. The distribution and type of errors were characterised. Results The 14 item sets of the fTORT form a well behaved unidimensional scale, and demonstrate excellent internal consistency (Cronbach alpha of 0.93). Deletion of any item failed to improve the Cronbach score. Most items displayed a bimodal score distribution; with function and attribute errors (score 0) or correct response (score 3) being most common. A smaller proportion of one- or two-attribute errors occurred. The total score range differentiated performance over a wide range of object recognition impairment. Conclusion Unidimensional scale and similar factor loadings across all items support simple addition of the 14 item scores on the fTORT. Therapists can use the fTORT to quantify impaired tactile object recognition in people with stroke based on the current set of items. New insights on the nature of haptic object recognition impairment after stroke are revealed.